Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/ejoc.201301137
|View full text |Cite
|
Sign up to set email alerts
|

1,6‐Enyne Cyclizations Catalyzed by N‐Heterocyclic Carbene Supported Gold Complexes: Deconvoluting Sterics and Electronics

Abstract: A series of N‐heterocyclic carbene (NHC) supported gold(I) complexes were synthesized, characterized in solution as well as in the solid state, and examined as precatalysts for 1,6‐enyne cycloisomerization reactions. The product mixtures obtained for a variety of 1,6‐enyne isomerizations were governed primarily by the electronic properties of the aforementioned precatalysts. In particular, precatalysts containing electronic‐rich NHC ligands showed increased selectivity for bicyclic products, whereas analogous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 62 publications
(15 reference statements)
0
26
0
Order By: Relevance
“…Aw hole equivalent of Et 3 SiH was now consumed by reactionw ith 1 in the presenceo fp hosphine. The proton NMR spectrum of 9 was consistentw itht he C s symmetric 6-MesDAC-Hl igand, the NCHNr esonance at d = 5.96 ppm now correlating to a 13 Cr esonance at d = 68.7 ppm, split into ad oublet with a 2 J CÀP coupling of 62 Hz. The IR spectrum showed carbonyl bandsf or 9 at 1662 and 1632 cm À1 ,a pproximately 80 cm À1 lower in frequency than those of 1 and 3 due to the loss of conjugationb etween the amide Nl one pairs and diamidomethine carbon centre.…”
Section: Attempted Formation Of [(6-nhc)cuh]mentioning
confidence: 57%
See 2 more Smart Citations
“…Aw hole equivalent of Et 3 SiH was now consumed by reactionw ith 1 in the presenceo fp hosphine. The proton NMR spectrum of 9 was consistentw itht he C s symmetric 6-MesDAC-Hl igand, the NCHNr esonance at d = 5.96 ppm now correlating to a 13 Cr esonance at d = 68.7 ppm, split into ad oublet with a 2 J CÀP coupling of 62 Hz. The IR spectrum showed carbonyl bandsf or 9 at 1662 and 1632 cm À1 ,a pproximately 80 cm À1 lower in frequency than those of 1 and 3 due to the loss of conjugationb etween the amide Nl one pairs and diamidomethine carbon centre.…”
Section: Attempted Formation Of [(6-nhc)cuh]mentioning
confidence: 57%
“…[20] The orange solution turned instantly dark red and then, within seconds, afforded ay ellow suspension. Thes olid component was identified by powder X-ray diffraction as nanoparticulate Cu 2 O( see the Supporting Information), whereas the 1 HNMR spectrum of the solution showedt he presence of as ingle copper-containing species( present alongside tBuOH), which was characterised by X-ray diffraction as ad ifferent ringopenedc arbene product, [(6-MesDAC)Cu(OC(O)CMe 2 C(O)N(H)- (1)ÀC (1) 1.874(2), Cu(1)ÀO (1) 1.8016 (15), O(1)ÀC (23)1 .407(3), C(1)ÀCu (1)-O(1) 175.31(8), Cu(1)-O(1)-C(23) 124.75 (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1241), followed by ring expansion, oxonium ion hydrolysis, and demetallation. The effect of ancillary 6-membered ring NHC ligands on the formation of fused cyclopropanes vs. ring opened compounds noted that the more electron-rich ligands afforded more of the cyclopropane compound [1183]. A computational study of enyne cycloisomerization followed by ring opening with ethanol was reported, emphasizing regioselectivity (5-vs 6-membered ring M a n u s c r i p t 151 formation) issues [1184].…”
Section: )mentioning
confidence: 96%
“…Bielawski and co‐workers explored the electronic effects of N ‐heterocyclic carbenes (NHCs) in gold complexes to tune the ratio of bicyclic versus olefin products for 1,6‐enyne cyclizations (Figure 12). 13 By designing NHCs that were sterically similar, they were able to separate steric and electronic effects on the reaction outcome. They found that 13 C NMR resonances of the carbenoid nuclei correlated with the Tolman electronic parameters, which are a measure of the electron‐donating properties determined by the frequency of the IR CO stretch.…”
Section: Organometallic Chemistrymentioning
confidence: 99%